PENGARUH DUKUNGAN LOGISTIK KRI JENIS BANTU CAIR MINYAK TERHADAP KETAHANLAMAAN OPERASI LAUT - Yudah Trismoyo; Prio Budi Leksono (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The purpose of this research is to find out how much influence the mobile logistics support by KRI BCM Type which includes fuel, fresh water and food support so that the presence in the sea of operational elements can be increased so that the operations carried out can be carried out more effectively and efficiently. The extent of the operation area is not balanced with the implementing elements and the existence of government policies related to B20 diesel fuel results in limited amounts of fuel in this area because the KRI elements who carry out the operation still use B0 (diesel) fuel. The distribution of logistical support from the front base to operational elements is still constrained by time, because most fuel logistical support is obtained through Pertamina tankers. Therefore, it is important for BCM elements to be held in selective operational areas so that the operational sustainability of the elements can be carried out more effectively and efficiently. The BCM element has the ability to provide logistical support, both in the form of liquid logistics support and personnel logistics support. This study uses a quantitative method carried out at the Fleet Command II with the object of research being KRI BCM Type and the subjects are crews of KRI BCM Type, Commanding Officers and Work Unit related to the implementation of KRI logistical support. Data obtained through the distribution of questionnaires were then analyzed using the Statistical Product dan Service Solutions (SPSS) version 25 program.